The historical and current roles of Street Committees in strengthening health services in Gugulethu - Chidavaenzi, Merlary (Department of Public Health and Family Medicine, 2021)
Communities are an important part of health systems as they assist in the monitoring of health service quality and providing the end users with a voice. This is particularly important in South Africa where there is a quadruple burden of disease, and a history of social injustice which continues to impact social determinants of health in communities. This presents significant challenges to provide high-quality health services in South Africa. To redress these health challenges, the South African government is relying on community-led mechanisms aimed at enhancing access to and strengthening of health services in communities. By using ethnographic methodologies, this paper explores the role of Street Committees (SC) in strengthening health services in a low-income setting in South Africa. The mini thesis is divided into two parts, a research protocol (Part A) and journal ‘ready' manuscript (Part B). Part A explores the historical, current, and future roles of SC in Gugulethu as well as identifying gaps in literature. Part B focuses on emerging roles from the data collected on SC in strengthening health services in Gugulethu. This thesis shows that although SC do not see themselves as health stakeholders nor are perceived by others as such, they do play a significant role, as they strengthen access to health care services through their numerous roles in the community. SC strengthen access to health services by enhancing physical access to health services, bringing medication to the frail and elderly, informing and educating the community about services and health issues and lastly by advocating for high quality health care in their community. This article also highlights the different roles SC play in strengthening health services through collaboration, advocacy and community education and provides lessons for community engagement in health systems which can be used to provide quality, equitable and people centred health care for all.